1994
DOI: 10.1002/cne.903470404
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord lamina V and lamina VII interneuronal projections to sympathetic preganglionic neurons

Abstract: This light and electron microscopic study sought to localize spinal cord interneurons that contribute to the normal and abnormal physiological regulation of spinal sympathetic preganglionic function. Sympathetic preganglionic neurons in caudal C8 through T4 of rat spinal cord were retrogradely labeled with wheat germ agglutinin (WGA) and/or cholera beta subunit (CT beta) following injections into the superior cervical ganglion (SCG). With two exceptions, the observed locations of retrogradely WGA- and CT beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 89 publications
(87 reference statements)
5
28
0
Order By: Relevance
“…The present results taken together with that of TOGASHI et al (1992) suggest that the fibres may arise from interneurons in lamina V (CABOT et al, 1991(CABOT et al, , 1994 and/or supraspinal regions. In the latter, it is possible that, besides the traditional monoamine-, amino acid-and peptide-containing axon terminals in ILp, there might exist yet other supraspinal projection fibres to the ILp with NO being utilized as a neurotransmitter or neuromodulator.…”
Section: Ultrastructural Localization Of Nadph-d Activitysupporting
confidence: 85%
“…The present results taken together with that of TOGASHI et al (1992) suggest that the fibres may arise from interneurons in lamina V (CABOT et al, 1991(CABOT et al, , 1994 and/or supraspinal regions. In the latter, it is possible that, besides the traditional monoamine-, amino acid-and peptide-containing axon terminals in ILp, there might exist yet other supraspinal projection fibres to the ILp with NO being utilized as a neurotransmitter or neuromodulator.…”
Section: Ultrastructural Localization Of Nadph-d Activitysupporting
confidence: 85%
“…A vast proportion of bulbospinal inputs directly innervate SPNs in the intermediolateral cell column (IML) (Anderson et al, 1989;Zagon and Smith, 1993;Pyner and Coote, 1998). However, viral trans-synaptic labeling studies have revealed many interneurons that are involved in sympathetic control in specific areas of the spinal cord, including the IML and laminas V and VII (Cabot et al, 1994;Joshi et al, 1995), and these are likely candidates for mediating indirect supraspinal control of SPN activity. Recently, putative presympathetic interneurons have also been located in the central autonomic area (CAA), dorsal and lateral to the central canal (Clarke et al, 1998;Tang et al, 2004), a region that receives input from vasomotor regions of the brain (Caverson et al, 1983;Bacon and Smith, 1993;Zagon and Smith, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…86.6 organisation. Also a small number only contained HSV-1-GFP, these were not SPNs because they were smaller in size and found in the white matter of the spinal cord in a region suggested to be where interneurones are located, (Cabot et al 1991(Cabot et al , 1994Joshi et al 1995). It is interesting that LaVail et al (1993) have reported that the retrograde tracer FG interferes with the infectivity of herpes simplex virus.…”
Section: Discussionmentioning
confidence: 99%